2019
DOI: 10.1007/s00216-019-01574-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determination of folates: recent analytical strategies and challenges

Abstract: Since the introduction of liquid chromatography tandem mass spectrometry in clinical laboratories, folate analysis has shifted from microbiological or protein binding assays to chromatographic methods. Now it is possible to sensitively and selectively determine several folate species in clinical samples where only a total folate content could be quantified using a microbiological or a binding assay. Although several chromatographic methods have been developed, validated and published, interlaboratory variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…This is especially relevant for folates, as they are well-known for their light sensitivity. 15,31 However, our analyses revealed that drying and/ or storage in the presence of light did not relevantly affect the individual folate levels when using VAMS samples. Only for the major folate vitamer 5MTHF and the minor folate vitamer 10FoFA a decrease was observed compared to drying in protected conditions, however the mean recovery relative to t 0 was still above 75% (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…This is especially relevant for folates, as they are well-known for their light sensitivity. 15,31 However, our analyses revealed that drying and/ or storage in the presence of light did not relevantly affect the individual folate levels when using VAMS samples. Only for the major folate vitamer 5MTHF and the minor folate vitamer 10FoFA a decrease was observed compared to drying in protected conditions, however the mean recovery relative to t 0 was still above 75% (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…O'Broin and Gunter hypothesized that this was caused by AA contributing to red blood cell lysis at the time of spotting and by enhancing deconjugation of red blood cell polyglutamates, resulting in an increased level of (less stable) folate monoglutamates. 15,32 This hypothesis implies that when red blood cells dry naturally on filter paper a greater stability would be achieved compared to using AA-treated paper. This is in contrast to serum, where folates are already present as monoglutamates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations